The brilliant reign of the Kangxi Emperor : China's Qing Dynasty - Hung, Hing Ming (Algora Publishing, 2017)
China's Qing Dynasty gave the fading glory of the Ming Dynasty a fresh and fabulous new start. From the early 1600s to the 1700s, a series of able leaders expanded and strengthened the realm, making China an economic and cultural powerhouse again. Important steps along the way are related in this straightforward narrative.